No experimental evidence of co-feeding transmission of african swine fever virus between Ornithodoros soft ticks - (:unkn) unknown (My University, 2020)
Ornithodoros soft ticks are the only known vector and reservoir of the African swine fever virus, a major lethal infectious disease of Suidae. The co-feeding event for virus transmission and maintenance among soft tick populations has been poorly documented. We infected Ornithodoros moubata, a known tick vector in Africa, with an African swine fever virus strain originated in Africa, to test its ability to infect O. moubata through co-feeding on domestic pigs. In our experimental conditions, tick-to-tick virus transmission through co-feeding failed, although pigs became infected through the infectious tick bite.
Keywords: African Research